Variability of rock mass support vs lengths of rockbolts - Giraldo Paredez, E. Mauro (2011)
This research is focused on establishing the load capacity of the rockbolts commonly used in Peru based on their length. Initially, we aimed to perform the pull tests on granite blocks at San Marcos University Campus, they were carried out under real operating mining conditions, at Reliquias, Castrovirreyna Mining Company (Huancavelica) during March of the current year. The rockbolts tested were: Split Set, Threaded Rebars, Hydrabolt and Swellex, which were suitably conditioned to have an effective anchorage of 1 to 4 feet. The Split Set and Threaded Rebars were cut and delivered as per our request by PRODAC and Aceros Arequipa, respectively. Both, Hydrabolt and Swellex rockbolts, supplied by New Concept Mining and Atlas Copco, were piped around to allow the anchorage of the established lengths only. Fifty one tests were carried (11 Split Set, 17 Threaded Rebars, 12 Hydrabolts and 11 Swellex), and the results showed that the load capacity of the rockbolts does not keep any linear relation with their length, that is to say, for example, when we duplicate the length of a rockbolt, its load capacity not necessarily will be doubled. The elongation of the bolts tends to keep a linear relation with the applied load. Split Set, Hydrabolt and Swellex rockbolts showed an uniform anchorage changing their lengths, whereas the Threaded Rebars showed an irregular anchorage, especially when they were installed with cement. The rockbolts of major and minor load capacity per length are the Hydrabolts and the Split Set, for a 2 feet bond length of anchorage their capacities were 15,75 ton and 3,75 ton, respectively. The bolt that showed less elongation was the Hydrabolt and the one with the greatest the Split Set. The Rockbolt of lowest cost for m2 supported was the Hydrabolt ($10,95/m2) and the one with the highest cost the Swellex ($50,67/m2), costs worked out for a 7 foot rockbolt, prices of April, 2011, and according to the operating conditions at Reliquias Mine.